Leveraging Smart Devices as News-Gathering Tools for Journalists - Abdullahi, Shehu Abdulkadir; Mary, Oyeleke Iyabo (ALSYSTECH Journal of Education Technology, 2024)
This research investigates the usage of smart devices as tools for news-gathering among journalists in NUJ Bauchi. The study was guided by three primary research objectives, the study explores the level of smart device usage, journalists’ attitudes toward these devices, and the various types of smart devices employed in journalism practices. A survey design was adopted for the study and data were collected from 218 journalists at NUJ Bauchi, and a comprehensive analysis of the responses was conducted. The findings revealed a high level of adoption of smart devices among journalists, with the majority of respondents acknowledging the integral role of smart devices in news-gathering. These devices have become indispensable tools in their daily routines, reflecting their seamless integration into journalistic practices. Furthermore, the study uncovers positive attitudes among journalists toward smart devices. Journalists recognize the transformative potential of these devices in journalism, acknowledging their influence on the editorial process, skill development, and news-gathering efficiency. Diverse smart device usage is another key revelation of this research. Various types of smart devices, ranging from digitalized/3D printers and laptops for print media to microphones, mixers, modern transmitters, smartphones, and cameras for audio, visual, and internet-based news coverage, are employed by journalists in Bauchi State. Therefore, the study recommends that stakeholders, including media organizations, journalism schools, and technology providers, maximize the benefits of smart devices in journalism.